(untitled) (Salud, Arte y Cuidado, 2021)
The purpose of this research was to reveal a corpus of adaptive strategies to parents and representatives of children with oncological pathology. For this purpose, the methodology assumed qualitative research in the hermeneutic phenomenological method. The key informants were 1 child, 1 parent or representative and 1 nursing staff. In reference to the source of information, it was the Hospital Universitario Pediátrico Agustín Zubillaga. For data collection, the interview and participant observation techniques were used. In addition, a semi-structured questionnaire-type instrument was developed that was applied to the children of the Dr. Agustín Zubillaga Pediatric University Hospital, specifically the oncology area. In this sense, to interpret from subjectivity, it was possible to explore, interpret and understand the experiences lived by the social actors from the beginning of the disease to their current life with it in the phenomenon under study. The information was interpreted in categories in order to make comparisons and a dialectical approach so that the information was organized and presented following an emerging guideline or regularity. Allowing to reflect that fathers, mothers and representatives as the only responsible guarantor of the biopsychosocial health of children, must stimulate favorable behaviors in the strengthening of physical and emotional well-being, through the various activities of motivation, integration, recreation, education and information. Hence, the needs presented by fathers, mothers and representatives are established with the purpose of setting action plans on specific aspects in the adaptive behaviors of children with oncological pathology, in order to create a corpus of adaptive strategies that allow them to have an effective and affective communication with the infants, for a good biopsychosocial development of the same.